Back Cover: Synthesis of Polyampholyte Janus‐like Microgels by Coacervation of Reactive Precursors in Precipitation Polymerization (Angew. Chem. Int. Ed. 3/2020). Issue 3 (16th December 2019) - Xu, Wenjing; Rudov, Andrey; Oppermann, Alex; Wypysek, Sarah; Kather, Michael; Schroeder, Ricarda; Richtering, Walter; Potemkin, Igor I.; Wöll, Dominik; Pich, Andrij
Abstract : The synthesis of stimuli‐responsive polyampholyte Janus‐like microgels using a template‐free, water‐based, and easily up‐scalable technique is reported by A. Pich et al. in their Research Article on page 1248 . The synthesis is based on the controlled self‐assembly and coacervation of growing polyelectrolyte microgel precursors during precipitation polymerization. The mixing time of the two solutions of growing microgel precursors determines the morphology of the polyampholyte microgels.